Nobody blinded me. Notes on the public and mediation in the performing arts. - Aquilué Laliena, Javier (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
Once the performing arts (happenning, performance) have been absorbed by the institutions, the aim of the avant-garde to integrate the public into the art process has been actively taken by art mediation. This text highlights several issues that may undermine these efforts, such as stablishing prearranged attitudes for the spectators to play, and scamping conflict, unproductive subjectivity, and the complexity of art for the sake of entertainment or possitive impact.
Keywords: performing arts; happening; performance; mediation; subjectivity; conflict; unproductiveness